S-17-4: EFFECTIVENESS OF STATIN INTENSIVE THERAPY IN TYPE 2 DIABETES WITH HIGH VISIT-TO-VISIT BLOOD PRESSURE VARIABILITY. (January 2023) - Ikeda, Shota; Shinohara, Keisuke; Enzan, Nobuyuki; Matsushima, Shouji; Tohyama, Takeshi; Funakoshi, Kouta; Kishimoto, Junji; Itoh, Hiroshi; Komuro, Issei; Tsutsui, Hiroyuki
Abstract : Objective: Intensive lipid-lowering therapy is recommended in type 2 diabetes mellitus (T2DM) patients with target organ damage. However, evidence is insufficient to stratify the patients who will benefit from the intensive therapy among them. High visit-to-visit variability in systolic blood pressure (SBP) is associated with increased risk of cardiovascular events. Thus, we hypothesized that the benefit of intensive lipid-lowering therapy is larger in T2DM patients with high visit-to-visit SBP variability who are considered at higher risk. This study aimed to investigate the effectiveness of intensive versus standard statin therapy in primary prevention of cardiovascular events among T2DM patients with retinopathy stratified by visit-to-visit SBP variability. Design and method: The EMPATHY study was the first randomized trial comparing statin intensive therapy targeting low- density lipoprotein cholesterol (LDL-C) < 70 mg/dL and standard therapy targeting LDLC ®100 to < 120 mg/dL in T2DM patients with retinopathy without known cardiovascular disease. Using this dataset, we divided the patients into two subpopulations based on standard deviation (SD) and average real variability (ARV) of clinic SBP within initial 6 months. The outcome was the composite incidence of cardiovascular events, including cardiac, cerebral, renal, and vascular events or death associated with cardiovascular events. Results: In a total of 4899 patients, 240 composite cardiovascular events were observed during a median follow-up of 37.3 months. The number of blood pressure measurements was 6.6 ± 1.6. The median value of SD and ARV of SBP was 9.78 mmHg and 10.29 mmHg, respectively. These median values were used as cutoffs. In multivariable-adjusted model comparing intensive versus standard therapy, the hazard ratios for composite cardiovascular events were 0.64 (95% CI 0.45–0.90, p = 0.012) and 1.21 (95% CI 0.82–1.80, p = 0.34) in patients with high and low SBP variability as defined by SD, respectively. Interaction between SBP variability and statin therapy was significant (p = 0.018). The analysis using ARV of SBP showed similar results (high ARV: hazard ratio 0.62, 95% CI 0.44–0.88, p = 0.008; low ARV: hazard ratio 1.15, 95% CI 0.78–1.70, p = 0.48; p for interaction = 0.022.). Conclusion: Statin intensive therapy targeting LDL-C < 70 mg/dL had benefits in primary prevention of cardiovascular events compared with standard therapy among T2DM patients with retinopathy having high, but not low, visit to visit SBP variability. Stratification based on visit-to-visit SBP variability might be a novel and useful strategy to determine the target LDL-C levels in statin lipid-lowering therapy among T2DM patients with microvascular complications.